Cross‐L* Coherence of the Outer Radiation Belt During Storms and the Role of the Plasmapause. Issue 10 (28th September 2021) - Walton, S. D.; Forsyth, C.; Rae, I. J.; Watt, C. E. J.; Thompson, R. L.; Horne, R. B.; Meredith, N. P.; Rodger, C. J.; Walach, M.‐T.; Clilverd, M. A.; Glauert, S. A.
Abstract: The high energy electron population in Earth's outer radiation belt is extremely variable, changing by multiple orders of magnitude on timescales that vary from under an hour to several weeks. These changes are typically linked to geomagnetic activity such as storms and substorms. In this study, we seek to understand how coherent changes in the radiation belt are across all radial distances, in order to provide a spatial insight into apparent global variations. We do this by calculating the correlation between fluxes on different L * measured by the PET instrument aboard the SAMPEX spacecraft for times associated with 15 large storms. Our results show that during these times, variations in the > 0.63 MeV electron flux are coherent outside the minimum plasmapause location and also coherent inside the minimum plasmapause location, when flux is present. However, variations in the electron fluxes inside the plasmapause show little correlation with those outside the plasmapause. During storm recovery and possibly main phases, flux variations are coherent across all L * regardless of plasmapause location, due to a rapid decrease, followed by an increase in radiation belt fluxes across all L * . Key Points: Near‐relativistic electron fluxes associated with storms are highly correlated ( r 2 > 0.8 ) cross‐ L * outside the minimum plasmapause location Electron fluxes inside the minimum location of the plasmapause are also well correlated but show little correlation with fluxes outside During storm main and recovery phases, the electron fluxes are well correlated across all L * irrespective of the plasmapause location